Are World Trade Organization members correctly applying World Trade Organization rules in safeguard determinations? - Stevenson, Cliff (2004)
Assesses the extent to which the growth in use of safeguards is legitimate or whether, the WTO safeguard provisions are currently being misapplied to provide illegal protection for domestic industries.